Modulating the tumor microenvironment with new therapeutic nanoparticles: A promising paradigm for tumor treatment. Issue 3 (11th November 2019) - Zhang, Yinlong; Ho, Shih‐Hsin; Li, Bozhao; Nie, Guangjun; Li, Suping
Abstract: To better make nanomedicine entering the clinic, developing new rationally designed nanotherapeutics with a deeper understanding of tumor biology is required. The tumor microenvironment is similar to the inflammatory response in a healing wound, the milieu of which promotes tumor cell invasion and metastasis. Successful targeting of the microenvironmental components with effective nanotherapeutics to modulate the tumor microvessels or restore the homeostatic mechanisms in the tumor stroma will offer new hope for cancer treatment. We here highlight the progress in constructing nanotherapeutics to target or modulate the tumor microenvironment. We discuss the factors necessary for nanomedicines to become a new paradigm in cancer therapy, including the selection of drugs and therapeutic targets, controllable synthesis, and tempo‐spatial drug release.